The Urgency of Child Custody of Divorce Victims in the Perspective of Customary Law in accordance with the Civil Code - Pradinata, Clara Agustin; Kazuo, Jeydhen; Kurniawan, Ivana (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Divorce is the legal breaking of the marriage bond between husband and wife. Divorce can cause child custody issues. The purpose of this study is to discuss the position of children in marriage and child custody as a result of divorce from the perspective of customary law according to the Civil Code. This research method is normative juridical, with data search techniques through literature review of books, legal sources and relevant scientific journals. The results explain that the position of children in marriage is divided into legitimate and illegitimate children. Determining child custody is an important thing to do after a divorce to avoid disputes. Laws on marriage, divorce and child custody are contained in Law No. 1 of 1974 Chapter XI, KHI Chapter XV and the religious courts contained in Law no. 50 of 2009. According to Law No. 1. of 1974 the responsibility of caring for children is the responsibility of both parents as long as the child is under 18 years of age and the parents' rights are not revoked, and according to KHI children under 12 years of custody fall on the mother but when they become adults they can choose custody. According to the Civil Code, the court has the authority to decide whether one of the parents becomes the owner of custody by considering the child's needs and child protection. Article 230 states that parents who are unable to exercise their custody rights have a permanent obligation to provide maintenance. Whereas customary law in determining child custody takes into account kinship, the child can be the custody of the father or mother, but when he becomes an adult he returns to customary custody, but when he is young custody falls on the mother and the father is still obliged to provide for the child until he is an adult.